2021
DOI: 10.3390/jcm10214857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Midazolam to Dual Prophylaxis for Preventing Postoperative Nausea and Vomiting

Abstract: Multimodal prophylaxis for postoperative nausea and vomiting (PONV) has been recommended, even in low-risk patients. Midazolam is known to have antiemetic properties. We researched the effects of adding midazolam to the dual prophylaxis of ondansetron and dexamethasone on PONV after gynecologic laparoscopy. In this prospective, randomized, double-blinded trial, 144 patients undergoing gynecological laparoscopic surgery under sevoflurane anesthesia were randomized to receive either normal saline (control group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Previous studies revealed that the incidence of PONV in these patients is as high as 40-80%. 19,20 However, our study revealed a PONV incidence of as low as 9.8%, which signi cantly improves postoperative satisfaction and promotes postoperative rehabilitation of patients.…”
Section: Dicussionmentioning
confidence: 58%
“…Previous studies revealed that the incidence of PONV in these patients is as high as 40-80%. 19,20 However, our study revealed a PONV incidence of as low as 9.8%, which signi cantly improves postoperative satisfaction and promotes postoperative rehabilitation of patients.…”
Section: Dicussionmentioning
confidence: 58%